Revolutionizing ornamental horticulture: Insights from the National Conference on smart farming solutions - Malohtra, S. K.; Goyal, Ramesh Kumar; Sindhu, S. S.; Pathania, Sabhya (Indian Horticulture, 2025)
The Indian Society for Ornamental Horticulture (ISOH) hosted a National Conference on Smart Farming Solutions for Ornamental Horticulture from November 8-9, 2024. It was held at Maharana Pratap Horticultural University (MHU), Karnal, Haryana. The event brought together over 500 participants, including scientists, industry leaders, students, and farmers, to discuss innovative practices and technologies in floriculture and landscaping.